1993
DOI: 10.1136/gut.34.8.1081
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow toxicity caused by azathioprine in inflammatory bowel disease: 27 years of experience.

Abstract: Myelosuppression is an important and potentially lethal complication of azathioprine treatment. The blood count has been reviewed in all patients treated with azathioprine for inflammatory bowel disease over 27 years in one hospital. Altogether 739 patients (422 with Crohn's disease, 284 with ulcerative colitis, and 33 with indeterminate colitis) were treated with 2 mg/kg/day azathioprine for a median of 12-5 months (range 0.5-132) between 1964 and 1991. Full blood counts were performed monthly for the duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
288
3
21

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(324 citation statements)
references
References 30 publications
9
288
3
21
Order By: Relevance
“…Myelosuppression is the most feared consequence and occurs in 1.4^5% of cases. 11,13,14 Some cases of mild myelosuppression can be resolved by dose reduction but more severe cases require immediate withdrawal. The most common adverse events are allergic reactions (2.3%), 11 which include a febrile myalgic reaction usually seen in the ¢rst two weeks of commencing the drugs.…”
Section: Thiopurine Toxicitymentioning
confidence: 99%
“…Myelosuppression is the most feared consequence and occurs in 1.4^5% of cases. 11,13,14 Some cases of mild myelosuppression can be resolved by dose reduction but more severe cases require immediate withdrawal. The most common adverse events are allergic reactions (2.3%), 11 which include a febrile myalgic reaction usually seen in the ¢rst two weeks of commencing the drugs.…”
Section: Thiopurine Toxicitymentioning
confidence: 99%
“…Maintenance therapy with in iximab, adalimumab, and certolizumab pegol is e ective (grade A). In iximab monotherapy and in iximab combined with azathioprine are more e ective than azathio-(e.g., leukopenia and thrombocytopenia) (214,215) . Pancreatitis, typically presenting several weeks a er initiating therapy, occurs in approximately 3 -15 % of patients and recurs with re-introduction of either azathioprine or mercaptopurine (17) .…”
Section: Maintenance Therapymentioning
confidence: 99%
“…Uncertainty regarding the risk for neutropenia deters some physicians from using AZA at effective doses and longer treatment with it. Experience abroad has shown that AZA can be safely used in treatment of CD and UC [25][26][27] . Recently, thiopurine methyltransferase (TPMT) and its genotype have been applied in predicting the myelotoxicity and reducing the incidence of leucopenia in Europe and North America [28][29][30] .…”
Section: Discussionmentioning
confidence: 99%